Genetic Dissection of the Major Quantitative Trait Locus (qSE11), and Its Validation As the Major Influence on the Rate of Stigma Exsertion in Rice (Oryza sativa L.) - Rahman, Md Habibur; Zhang, Yingxing; Zhang, Keqin; Rahman, Md Sazzadur; Barman, Hirendra N.; Riaz, Aamir; Chen, Yuyu; Wu, Weixun; Zhan, Xiaodeng; Cao, Liyong; Cheng, Shihua (Frontiers in Plant Science, 2017)
The rate of stigma exsertion is an important trait in rice breeding because the efficiency of hybrid rice seed production can be improved by increasing the percentage of stigmas that exsert. In this study, we developed a near isogenic line (NIL) from two parents, XieqingzaoB (XQZB) and Zhonghoi9308 (ZH9308), which have high and low stigma exsertion rates in that order. In our previous study, we employed 75 chromosome segment substitution lines (CSSLs) and analyzed quantitative trait loci (QTLs) for their influence on stigma exsertion rate. The single gene QTL (qSE11), which is located on chromosome 11, was responsible for this trait. In this study, we focused on one of the CSSLs (C65), namely, the NIL (qSE11XB). It contains an introgression segment of XQZB in the genetic background of ZH9308, and exhibits a significantly higher stigma exsertion rate than that of the parents. We demonstrated that qSE11 regulated both the single and the dual stigma exsertion rates. They both contribute to the total stigma exsertion rate. Genetic analysis revealed that qSE11 acted as a single Mendelian factor and that the allele from XQZB increased the stigma exsertion rate. The validity of our conclusions was established when C65 was used to develop secondary F2 (BC5F2) and F2:3 (BC5F2:3) populations by backcrossing to ZH9308, with subsequent selfing. We entered 3600 plants from the F2 population and 3200 from the F2:3 populations into a genetic dissection program and dissected the major QTL qSE11 to a 350.7-kb region located on chromosome 11. This study will contribute to the future isolation of candidate genes of stigma exsertion and will play a vital role in future hybrid rice seed production programs.